BIOSYNTHESIS OF SILVER NANOPARTICLES FROM MARINE POLYCHAETE DIOPATRA CLAPAREDII GRUBE, 1878 (Jurnal Teknologi (Sciences & Engineering), 2018)
Silver nanoparticles (AgNPs) offer a broad range of high commercial value applications. However, current techniques to synthesize AgNPs using chemical and physical approaches are toxic to the environment and not cost-effective in the long-term. Therefore, utilization of green biological synthesis technique to produce AgNPs is one of the solutions. In this study, marine polychaete Diopatra claparedii was used to investigate its potential in synthesizing AgNPs. Specimens were collected from tidal flats adjacent to the mangrove forest in the west coast of Peninsular Malaysia and divided into two groups: freshly prepared (acclimatized in aquaria) and frozen (kept in the freezer) samples. Samples from both groups were cut, finely pulverized, filtrated, and mixed with silver nitrate (AgNO3) at room temperature. Colour changes were recorded after 24 hours, 2 weeks, and 8 weeks of incubation. Formation of AgNPs was quantified using UV-Vis spectroscopy analysis, where surface Plasmon resonance (SPR) peaks were observed in the range of 400–440 nm, confirming the formation of the AgNPs. Subsequently, the synthesized nanoparticles were validated using scanning electron microscope. AgNPs showed weak antibacterial activity because of aggregation. Further studies are required to confirm the findings.